Tracking an omnidirectional evader with a differential drive robot at a bounded variable distance - Ruiz, Ubaldo; Marroquin, Jose Luis; Murrieta-Cid, Rafael (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we address the pursuit-evasion problem of tracking an Omnidirectional Agent (OA) at a bounded variable distance using a Differential Drive Robot (DDR), in an Euclidean plane without obstacles. We assume that both players have bounded speeds, and that the DDR is faster than the evader, but due to its nonholonomic constraints it cannot change its motion direction instantaneously. Only a purely kinematic problem is considered, and any effect due to dynamic constraints (e.g., acceleration bounds) is neglected.
Keywords: pursuit-evasion; tracking; capturing; differential drive robot